Illuminating the ethical tensions in the obesity Canada website: a transdisciplinary social justice perspective. Issue 5 (20th October 2021) - Kanagasingam, Deana; Norman, Moss; Hurd, Laura
ABSTRACT: Even though considerable resources have been allocated to the study of obesity, there is no consensus on its definition, causes, or solutions. Amidst ongoing debates over understandings of obesity, Obesity Canada (OC) was established to enhance the quality of life of Canadians with obesity through the advancement of anti-discrimination, policy change, and obesity prevention and treatment. Drawing upon a transdisciplinary social justice framework, we use critical thematic analysis to examine the OC website, which is the organization's primary knowledge mobilization platform. We will address the following research question: To what extent does OC serve social justice goals that promote the best interests of larger people? We argue that the social justice potential of OC ultimately falls short and conclude with some recommendations on how the site content could be enhanced with social justice principles.